Assessment of Bacterial Contamination and Health Risks Associated With Prolonged Use of Face Masks in Industry Settings - Osman, Baderin; Mahmud, Haalah; Mazlan, Sytty Mazian; Aqma, Wan Syaidatul (Malaysian Applied Biology, 2026)
Face masks are a critical component of Personal Protective Equipment (PPE) for occupational safety and health management. Nevertheless, prolonged usage of face masks may expose employees to biological contaminants, such as bacteria, which accumulate on the inner surface of the mask and pose potential health risks. This study involved 216 participants employed by a statutory institution in Malaysia. The participants were assigned to wear three types of face masks: cotton, surgical, and Korean filters for durations of four and eight hr during their respective work shifts, which varied across roles such as office workers, trainers, and cleaners. Bacterial isolates from the masks were analyzed using the MALDI-TOF method for species identification. Twelve bacterial species were successfully identified, including Staphylococcus hominis, Staphylococcus epidermidis, Staphylococcus ureilyticus, Bacillus velezensis, Dermacoccus nishinomiyaensis, Bacillus licheniformis, Acinetobacter variabilis, Micrococcus luteus, Bacillus pumilus, Bacillus cereus, Sporosarcina luteola, and Staphylococcus aureus. Most of these species are part of the normal human microbiota but have the potential to act as opportunistic pathogens. Additionally, other bacterial species, particularly spore-forming ones, may have originated from the work environment. To mitigate microbial risks, individuals performing strenuous physical tasks or those with compromised immunity are advised to avoid reusing face masks and to replace them every four hr.